Stapled transanal rectal resection (STARR) for obstructive defaecation syndrome: patients with previous pelvic floor surgery have poorer long‐term outcome. (27th March 2013) - Adams, K.; Papagrigoriadis, S.
Abstract: Aim: Stapled transanal rectal resection (STARR) is used for patients with obstructive defaecation syndrome (ODS) not responding to conservative management. Reports indicate mixed results and there are no studies publishing the long‐term outcome. Method: Following full investigation, 37 patients with ODS underwent a STARR procedure by one of the authors (SP) between 2005 and 2010. Results: The median (range) patient age was 53.0 (28–79) years and all were female. Median (range) follow up was 13 (0–57) months, and nine (24.3%) patients were followed for longer than 24 months. Eighteen patients had undergone at least one (and often multiple) previous gynaecological procedures, including hysterectomy ( n = 14), colposuspension ( n = 3), vaginal rectocele repair ( n = 4) and pelvic floor repair ( n = 5). Four patients had had at least one previous rectal operation [stapled anopexy ( n = 3) and Delorme's procedure ( n = 2)]. One patient did not attend for postoperative follow up. Of the remaining 36 patients, 18 had resolution of obstructive symptoms. Of the 18 with residual symptoms, 17 eventually reported the same level of symptoms as before the STARR procedure. There was a significant correlation between the presence of residual symptoms and long‐term ODS recurrence ( P < 0.0005). For those with residual symptoms, the mean (95% CI) time to symptom recurrence was 3 (2.86–11.81) months. Twenty (56%) patients were satisfied with the outcome from the STARR procedure. Conclusion: Residual symptoms are a strong indicator of long‐term failure. STARR was effective for symptom resolution in 50% of patients. Those who had undergone pelvic floor or rectal prolapse surgery were significantly more likely to experience recurrent symptoms.